Integration of Triple Bottom Line In Supplier Selection Process (Case Study at Indonesia Bottled Water Company) - Aditya Asmara Nala; Harianto; Popong Nurhayati (School of Business, IPB University (SB-IPB), 2023)
PT ABC is an Indonesia bottled water company that continues to strive to adopt sustainability efforts in every aspect of its business process, including on their supplier selection process. This study aims to determine the usage of TBL criteria in current formulation of supplier selection decisions at PT Tirta Investama; to determine what are the TBL integrated selection criteria and its assessment indicators which needed to select suppliers appropriately; and how to use them to select suppliers at PT ABC. Researchers conducted in-depth interviews with 4 procurement managers of PT ABC to find out the usage of TBL criteria in current formulation of supplier selection decisions. Currently, economic perspective still becomes the only one focus in supplier evaluation process in PT ABC. In fact, environmental and social concern still not significantly underlie supplier evaluation process which lead to selection decisions. The determination of TBL integrated selection criteria and its assessment indicators begins through literature review and finalized with focus group discussion (FGD). In this study, researchers established 13 TBL integrated selection criteria and 20 assessment indicators to select suppliers at PT ABC. Those criteria and indicators are then used to select suppliers in 4 main material categories of PT ABC using the analytical hierarchy process (AHP) method. Based on this selection process, a ranking of suppliers of each material category is obtained, resulting in PT A2 as top selected supplier in gallon bottle category, PT B1 as top selected supplier in gallon cap category, PT C1 as top selected supplier in preform category, and PT D1 as top selected supplier in screw cap category. Keywords: AHP, business sustainability, supplier selection, supplier selection criteria, triple bottom line